2020
DOI: 10.1007/s00122-020-03635-8
|View full text |Cite
|
Sign up to set email alerts
|

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy

Abstract: Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Even if these later CCA hybrids are more difficult to generate [76], improved recombination between homologous C chromosomes would also strongly benefit B. napus breeding programs. In fact, different studies revealed that it could be useful to introduce into B. napus new diversity from B. oleracea [77], such as clubroot resistance traits [78], and conversely from B. napus to B. oleracea [79]. It will also be interesting to determine if this modified homologous recombination landscape is also present in the other possible allotriploids from the U triangle [80], e.g., either AAB (deriving from B. juncea × B. rapa) or CCB (B. carinata × B. oleracea) hybrids, and thus possibly be useful for Brassica breeding.…”
Section: Development Of the Strategy On Other Modelsmentioning
confidence: 99%
“…Even if these later CCA hybrids are more difficult to generate [76], improved recombination between homologous C chromosomes would also strongly benefit B. napus breeding programs. In fact, different studies revealed that it could be useful to introduce into B. napus new diversity from B. oleracea [77], such as clubroot resistance traits [78], and conversely from B. napus to B. oleracea [79]. It will also be interesting to determine if this modified homologous recombination landscape is also present in the other possible allotriploids from the U triangle [80], e.g., either AAB (deriving from B. juncea × B. rapa) or CCB (B. carinata × B. oleracea) hybrids, and thus possibly be useful for Brassica breeding.…”
Section: Development Of the Strategy On Other Modelsmentioning
confidence: 99%
“…In addition, previous studies have shown that Ogura CMS and Kos CMS have the same restorer gene (Rfo/Rfk) [62], so the fertility of Bel CMS is likely to be restored by this restorer gene. We have hybridized Bel CMS with a fertile line containing the Rfo gene [1,63], and the fertility was successfully recovered, which showed that all three kinds of CMS can be fertility-restored by the same Rfo gene.…”
Section: Comparison Of Sterility Genes Between Ogura Cms and Bel Cms ...mentioning
confidence: 98%
“…capitata) is an important leafy vegetable crop that is widely cultivated worldwide. As a typical cross-pollinated plant, cabbage exhibits noticeable heterosis, and hybrids usually have better growth potential, yield, and disease resistance than their parents [1]. The utilization of heterosis in Brassica crops depends mainly on either self-incompatible or male-sterile lines [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rfo restorer gene was introduced from B. napus to B. oleracea by the bridge material Brassica alboglabra Bailey [ 80 , 81 , 82 ]. Using triploid and hexaploid methods, several Ogura CMS fertility-restored plants of B. alboglabra Bailey were successfully created.…”
Section: Application Of Ogura Cms and Creation Of Ogura Cms Fertility...mentioning
confidence: 99%